A Meandering Lunar Wake Produced by the Pickup of Reflected Solar‐Wind Ions. Issue 24 (20th December 2021) - Zhang, Hui; Zhong, Jun; Zhang, Tianxin; Liu, Libo; Cao, Jinbin; Fu, Suiyan; Wei, Yong; Chen, Yiding
Abstract: By establishing two solar‐wind convection electric field‐associated coordinate systems, the magnetic and plasma properties in the lunar wake are examined. In the plane perpendicular to the interplanetary magnetic field, all the properties exhibit asymmetric distributions related to the electric field, and they are even periodically modulated every two lunar radii but only along the flank which the electric field points to. Evidences show that the solar‐wind ions, reflected over the dayside lunar magnetic anomalies, have produced these asymmetries and periodical modulations. These ions, undergoing both the electric drift and large‐radius gyration, bypass the Moon body and periodically penetrate into the wake flank, during which they exchange momentum with the refilling solar‐wind plasma, thereby resulting in the oscillations of the plasma and the periodical modulations of the wake. Plain Language Summary: The lunar wake, produced by the solar‐wind plasma absorption on the dayside lunar surface, has been expected to be symmetric about the plane of the solar‐wind velocity and the interplanetary magnetic field. The solar‐wind convection electric field, which is perpendicular to that plane, has been found to be able to make asymmetric magnetic perturbations but only ahead of the lunar terminator, its influences to the magnetic field in the downstream wake, however, have not been noticed, yet. In this study, the reflected solar‐wind ions from the dayside lunar surface, biased and accelerated by the solar‐wind electric field, are found to be able to bypass the Moon, periodically penetrate into the wake flank which the electric field points to, and modulate the refilling plasma in the direction perpendicular to the magnetic field. The periodical modulations, thereby, produce an asymmetric and meandering wake as observed. Key Points: The central lunar wake meanders in phase with the gyromotions of the reflected ions in the solar‐wind The reflected solar‐wind ions periodically modulate the wake refilling plasma, thereby producing the meandering wake The magnetic field and the plasma properties in the wake are all modulated along with the meandering structure